Screening of Chinese giant salamander meat hydrolysates with DPP-Ⅳ inhibitory activity and systematic elucidation of their hypoglycemic functions in mouse model - Shucheng Li; Changge Guan; Yi Wang; Haihong Chen; Wei Li; Songjun Wang; Chong Zhang; Xinhui Xing (Food Science and Human Wellness)
Type 2 diabetes (T2D) presents a significant health challenge, underscoring the need for functional foods and nutraceutical hypoglycemic bioactive peptides for its prevention. This study investigates the potential of proteolytic hydrolysate from artificially cultivated Chinese giant salamander (CGS) meat, a rich protein source, as a preventive strategy for T2D. We produced a CGS meat hydrolysate (CGSh) and demonstrated its ability to inhibit the T2D drug target dipeptidyl peptidase Ⅳ (DPP-Ⅳ) through in vitro assays. We identified 5 peptides (WRPPDH, WAPPSKD, IPDSPF, IPEMIF, and VPIAVPT) with high DPP-Ⅳ inhibitory activity in CGSh, suggesting its potential antidiabetic effects. In vivo experiments showed that CGSh effectively reduced insulin resistance in mice induced with a high-fat diet, as evidenced by a slower increase in blood glucose levels and a decreased HOMA-IR index. 16S rRNA sequencing analysis revealed that CGSh improved gut microbial homeostasis, promoting beneficial microorganisms and reducing harmful bacteria. Metabolomic analyses identified an increase in valeric acid levels and highlighted nine potential biomarker metabolites. By inhibiting metabolic pathways such as AGE-RAGE, CGSh might also prevent diabetic complications and reduce inflammation. These findings suggest that CGSh has a promising hypoglycemic effect, making it a potential functional food ingredient for T2D prevention and treatment.